Elevation‐dependent responses of streamflow to climate warming. Issue 6 (9th May 2014) - Tennant, Christopher J.; Crosby, Benjamin T.; Godsey, Sarah E.
Abstract Warming will affect snowline elevation, potentially altering the timing and magnitude of streamflow from mountain landscapes. Presently, the assessment of potential elevation‐dependent responses is difficult because many gauged watersheds integrate drainage areas that are both snow and rain dominated. To predict the impact of snowline rise on streamflow, we mapped the current snowline (1980 m) for the Salmon River watershed (Idaho, USA) and projected its elevation after 3 °C warming (2440 m). This increase results in a 40% reduction in snow‐covered area during winter months. We expand this analysis by collecting streamflow records from a new, elevation‐stratified gauging network of watersheds contained within high (2250–3800 m), mid (1500–2250 m) and low (300–1500 m) elevations that isolate snow, mixed and rain‐dominated precipitation regimes. Results indicate that lags between percentiles of precipitation and streamflow are much shorter in low elevations than in mid‐ and high‐elevation watersheds. Low elevation annual percentiles (Q25 and Q75) of streamflow occur 30–50 days earlier than in higher elevation watersheds. Extreme events in low elevations are dominated by low‐ and no‐flow events whereas mid‐ and high‐elevation extreme events are primarily large magnitude floods. Only mid‐ and high‐elevation watersheds are strongly cross correlated with catchment‐wide flow of the Salmon River, suggesting that changes in contributions from low‐elevation catchments may be poorly represented using mainstem gauges. As snowline rises, mid‐elevation watersheds will likely exhibit behaviours currently observed only at lower elevations. Streamflow monitoring networks designed for operational decision making or change detection may require modification to capture elevation‐dependent responses of streamflow to warming. Copyright © 2014 John Wiley & Sons, Ltd.